Incidental findings on panoramic radiography (Research, Society and Development, 2022)
A large number of soft tissue calcifications in the head and neck region can be routinely identified by imaging tests, especially panoramic radiography, an exam widely used for analysis of the maxillomandibular complex. The evaluation of this exam requires from the professional a vast anatomical knowledge of the craniofacial regions and of the possible incidental findings. Thus, this study aimed to review the literature concerning incidental findings commonly found on panoramic radiographs. Bibliographic search of studies published from 2016 to 2021 carried out in Pubmed, Lilacs, SciELO and Google Scholar databases using the controlled descriptors "panoramic radiography", "incidental findings", "vascular calcification". he main findings described in the literature are: carotid artery atheromas, phleboliths, sialoliths, tonsilloliths, and calcifications of the stylohyoid complex. Carotid atheromas and stylohyoid complex calcifications have a higher incidence. The misinterpretation of an incidental finding or simply non-compliance can trigger greater damage to the patient's health as oral health interferes with systemic health.